2019
DOI: 10.1111/jam.14239
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite of endophytic fungus Cadophora orchidicola from Kalimeris indica serves as a potential fungicide and TLR 4 agonist

Abstract: Aim To investigate the bioactive metabolite of endophytic fungus from Kalimeris indica. Methods and Results A strain ZJLQ336 was separated from the leaves of K. indica. It was identified as Cadophora orchidicola based on the phylogenetic analysis of ITS‐rDNA sequences. From the fermentation broth a metabolite cercosporamide (compound 1) was isolated, and its structure was determined by spectroscopic analysis. Additionally, this compound was subjected to bioactivity assays, including antifungal activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moreover, both of them also displayed potent inhibitory effects against mycelial growth of Pythium ultimum, Aphanomyces cochlioides , and R. solani ( Talontsi et al, 2012 ). A metabolite cercosporamide (30) was isolated from the endophytic fungus Cadophora orchidicola from Kalimeris indica ( Wang et al, 2019 ). Antifungal assay revealed that 30 had potent growth inhibition against five plant pathogens, Pestalotia diospyri, B. cinerea, Fusarium oxysporum, Sclerotium rolfsii , and Penicillum digitatum , with EC 50 values of 16.0 × 10 –3 , 1.8, 2.8, 2.89, and 20.2 μM, respectively ( Wang et al, 2019 ).…”
Section: Chemical Diversity Of Antifungal Secondary Metabolites From Endophytic Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both of them also displayed potent inhibitory effects against mycelial growth of Pythium ultimum, Aphanomyces cochlioides , and R. solani ( Talontsi et al, 2012 ). A metabolite cercosporamide (30) was isolated from the endophytic fungus Cadophora orchidicola from Kalimeris indica ( Wang et al, 2019 ). Antifungal assay revealed that 30 had potent growth inhibition against five plant pathogens, Pestalotia diospyri, B. cinerea, Fusarium oxysporum, Sclerotium rolfsii , and Penicillum digitatum , with EC 50 values of 16.0 × 10 –3 , 1.8, 2.8, 2.89, and 20.2 μM, respectively ( Wang et al, 2019 ).…”
Section: Chemical Diversity Of Antifungal Secondary Metabolites From Endophytic Fungimentioning
confidence: 99%
“…A metabolite cercosporamide (30) was isolated from the endophytic fungus Cadophora orchidicola from Kalimeris indica ( Wang et al, 2019 ). Antifungal assay revealed that 30 had potent growth inhibition against five plant pathogens, Pestalotia diospyri, B. cinerea, Fusarium oxysporum, Sclerotium rolfsii , and Penicillum digitatum , with EC 50 values of 16.0 × 10 –3 , 1.8, 2.8, 2.89, and 20.2 μM, respectively ( Wang et al, 2019 ). Two new solanapyrone analogs, solanapyrones N (31) and O (32), and the known solanapyrone C (33), were isolated from Nigrospora sp.…”
Section: Chemical Diversity Of Antifungal Secondary Metabolites From Endophytic Fungimentioning
confidence: 99%
“… Verticillium dahliae A IV 49% [ 109 ] 5-(Undeca-3′,5′,7′-trien-1′-yl) furan-2-carbonate 12% Bicolorin D Saccharicola bicolor Sclerotinia sclerotiorum A IV 13% [ 110 ] IP-A 57% Brefeldin A Cladosporium sp. Aspergillus niger A IV 8-fold [ 111 ] Cercosporamide Cadophora orchidicola Fusarium oxysporum Pestalotia diospyri Botrytis cinerea Sclerotium rolfsii Penicillium digitatum A IV - [ 112 ] Cuminic acid Aspergillus spp. Phytophthora spp.…”
Section: Secondary Metabolites Of Fungi With Antifungal Propertiesmentioning
confidence: 99%
“…Cadophora orchidicola was originally described as a root endophyte of the orchid Platanthera hyperborean [57]. However, the fungus has also been found as an endophyte in the roots of various other plants from various plant families, such as Littorella uniflora (Plantaginaceae), a plant found on the sandy shores of freshwater lakes [58], Kalimeris indica (Asteraceae) [59], Colobanthus quitensis (Caryophyllaceae), and Deschampsia antarctica (Poaceae) in Antarctica [60]. The effects of C. orchidicola on their hosts are not fully understood.…”
Section: Non-pac Dsementioning
confidence: 99%
“…However, S. involucrata inoculated with the fungus grew to be significantly larger and had a greater biomass. The metabolite cercosporamide, produced by C. orchidicola, was shown to possess fungicidal properties against Pestalotia diospyri, Botrytis cinerea, Fusarium oxysporum, Sclerotium rolfsii, and Penicillium digitatum [59].…”
Section: Non-pac Dsementioning
confidence: 99%